Soccer Player robot CR7 - Ayman, Ghanem; Ameen, odah (My University, 2017)
CR7 is an autonomous obstacle avoidance robot specially designed and constructed for playing soccer in the small-size and fixed area according to rules and regulations. This robot consists of a moving mechanism, motion-control and obstacle avoidance hardware, software, .Motion control is carried out by a special control board that uses microcontroller to carry out the software system decisions and transfers them to the robot mechanics using sensors in order to find ball and still catch it until reach the goal. The objective of this project is pure entertainment using completely autonomous robot. We are planning to use Raspberry PI 3, Ultrasonic sensor, car body, DC Motors, Raspberry Camera and many other electronic and mechanical components.